The study on schedule policy of data transferring in storage network. (3rd January 2011) - Hu, Diqing; Cao, Qiang; Xie, ChangSheng
The I/O routine in network storage has longer transferring time and overhead than local I/O. To make good use of the storage network bandwidth and meet demand of concurrent I/O requests, we need to find the appropriate schedule policy for I/O requests at the level of the network. The focus in the paper is on how to schedule concurrent I/O data transferring in share storage network, and to improve performance such as the response time affected by scheduling method. Our objective is to analyse the response time of concurrent requests as function of their schedule order such as the sequenced, parallel and hybrid policies. We then verify our results by both the analytical and experimental method.